Clearly Irrational Financial Market Behavior: Evidence from the Early Exercise of Exchange Traded Stock Options - Poteshman, Allen M.; Serbin, Vitaly (Journal of Finance, 2003)
This paper analyzes the early exercise of exchange‐traded options by different classes of investors over the 1996 to 1999 period. A large number of exercises are identified as clearly irrational without invoking any model of market equilibrium. Customers of discount brokers and customers of fullservice brokers both engage in a significant number of irrational exercises while traders at large investment houses exhibit no irrational early exercise behavior. Rational and irrational exercise is triggered for discount and full‐service customers by the underlying stock price attaining its highest level over the past year and by high returns on the underlying stock.